Stem cells in adult human ovaries: from female fertility to ovarian cancer - Virant-Klun, Irma; Stimpfel, Martin; Skutella, Thomas (Current pharmaceutical design, 2012)
The human ovary is a complex endocrine gland, which is responsible for production of different hormones and provides mature and competent oocytes for repro...